What role for property taxes in Ireland? - Callan, Tim; Keane, Claire; Walsh, John R. (Economic & Social Studies, 2010)
What role could a property tax play in broadening the Irish tax base? An annual tax on property has been recommended in a series of reports over the past 25 years, from the first Commission on Taxation (1985), to the recent second Commission on Taxation (2009) and OECD (2009). As yet, however, a property tax has not been implemented. One of the key objections raised is that a property tax would be ?unfair?, in that it would not take account of ability to pay. In this paper we examine how a property tax could be designed to address this issue, drawing on the CSO?s EU SILC, which contains information on both incomes and housing values. We use an extended version of SWITCH, the ESRI tax-benefit model, to simulate the impact of alternative property taxes, and explore their revenue and distributional consequences in a static framework. This helps also to shed light on the geographic distribution of property tax revenues, an issue which came to prominence in the Residential Property Tax of the 1990s. The acronym stands for Simulating Welfare and Income Tax CHanges.
Policy paper
Keywords: Property taxation; Ireland; Fiscal policy; Tax incidence